(untitled) (Malaysian Journal of Civil Engineering, 2018)
This paper presents the results of an experimental investigation of the compressive strength of blended cement mortar cubes containing termite mound and lime. Two mix ratios of 1:4 and 1:6 (cement: sand) with water-cement ratio of 0.65, and varying combination of termite mound and lime in equal amount ranging from 10% to 50% replacing cement were used. A total of 900 cubes were cast, cured in water, H2SO4 and HNO3 for 7, 14, 21, 28 and 56 days in each medium. Test results showed that the compressive strength of the mortar cubes increases with age and decreases with increasing percentage replacement of cement with Termite mound-lime specimens cured in water; whereas, the compressive strength decreases with increase in age, percentage replacement of cement with termite mound-lime as well as solution concentration when the specimens were immersed in acidic solution. The study concluded that termite moundlime blended cement mortar is adequate for use as type S or N masonry mortar for construction purposes in non-acidic aggressive environment.